Review of the mechanical and fracture behavior of perovskite lead-free ferroelectrics for actuator applications. (2nd May 2017) - Webber, Kyle G; Vögler, Malte; Khansur, Neamul H; Kaeswurm, Barbara; Daniels, John E; Schader, Florian H
Abstract: There has been considerable progress in the development of large strain lead-free perovskite ferroelectrics over the past decade. Under certain conditions, the electromechanical properties of some compositions now match or even surpass commercially available lead-containing materials over a wide temperature range, making them potentially attractive for non-resonant displacement applications. However, the phenomena responsible for the large unipolar strains and piezoelectric responses can be markedly different to classical ferroelectrics such as Pb(Zr, Ti)O3 and BaTiO3 . Despite the promising electromechanical properties, there is little understanding of the mechanical properties and fracture behavior, which is crucial for their implementation into applications where they will be exposed to large electrical, mechanical, and thermal fields. This work discusses and reviews the current understanding of the mechanical behavior of large-strain perovskite lead-free ferroelectrics for use in actuators and provides recommendations for further work in this important field.